Woody vegetation of a Peruvian tropical dry forest along a climatic gradient depends more on soil than annual precipitation - Muenchow, Jannes; von Wehrden, Henrik; Rodríguez, Eric Frank; Arisméndiz Rodríguez, Rodolfo; Bayer, Fabian; Richter, Michael (ERDKUNDE, 2013)
Tropical dry forests are the most threatened ecosystem in the tropics. Tropical dry forests possess an outstanding beta diversity, which can live up to rain forests standards, yet they are still vastly understudied. In northern Peru, El Niño Southern Oscillation (ENSO) fundamentally shapes these unique and highly endemic ecosystems. The objective of this study was to determine (i) if a main gradient was detectable in the woody plant composition in this hyper- to semi-arid environment; and (ii) to which extent climatic and edaphic variables account for it. Sampling was done on 50 30 × 30 m2 random plots along a humidity gradient. A sodium-soil texture gradient correlated with the first Isomap axis. Potassium and pH, mainly representing precipitation, characterized the second axis. A cluster analysis detected two plant functional groups: a tropical desert formation and a shrub and dry forest formation. Variation partitioning revealed edaphic variables to be more important in structuring vegetation than mean annual rainfall. Extending irrigation in parts of the study area may possibly be beneficial for local residents. However, it will almost certainly trigger the extinction of the last remnants of the highly endemic tropical dry forest formations.